Highly Sensitive Gas and Ethanol Vapor Sensors Based on Carbon Heterostructures for Room Temperature Detection - Kočí, Michal; Wrobel, Pawel S; Godzierz, Marcin; Szabó, Ondrej; Pusz, Sławomira; Potocký, Štěpán; Husák, Miroslav; Kromka, Alexander (ACS applied materials & interfaces, 2025)
Graphene oxides (GOs) and hydrogen-terminated nanocrystalline diamonds (H-NCD) have attracted considerable attention due to their unique electronic structure and extraordinary physical and chemical properties in various applications, including gas sensing. Currently, there is a significant focus on air quality and the presence of pollutants (NH3, NO2, etc.), as well as volatile organic compounds (VOC) such as ethanol vapor from industry. This study examines the synthesis of GO, reduced graphene oxide (rGO), thiol-functionalized graphene oxide (SH-GO), and H-NCD thin films and their combination in heterostructures. The materials were analyzed for their ability to detect NO2, NH3, and ethanol vapor at room temperature (22 °C). Among the tested materials, the SH-GO/H-NCD heterostructure exhibited the highest sensitivity, with approximately 630% for ethanol vapor, 41% for NH3 and -19% for NO2. The SH-GO/H-NCD heterostructure also demonstrated reasonable response (272 s) and recovery (34 s) times. Cross-selectivity measurements revealed that the heterostructure's response to ethanol vapor at 100 ppm remained dominant and was minimally affected by the presence of NH3 (100 ppm) or CO2 (100 ppm). The response variations were -1.3% for NO2 and 2.4% for NH3, respectively. These findings suggest that this heterostructure has the potential to be used as an active layer in low-temperature gas sensors. Furthermore, this research proposes a primary mechanism that explains the enhanced sensor response of the heterostructure compared with bare GOs and H-NCD layers.
Keywords: hydrogen-terminated nanocrystalline diamond; gas sensor; ethanol vapor detection; reduced graphene oxide; graphene oxide; thiol-functionalized graphene oxide